Social Cognition Approach: Using Observation and Interview Methods via Qualitative Research - Mehrad, Aida; Nguyen, Kaden; Dihii, Joyce B. (Papanda Publisher, 2024)
This study focuses on social psychology and uses the social cognition approach and qualitative observational and interview methods to observe and analyze random individuals in public settings. Likewise, it aims to identify patterns, social dynamics, and psychological phenomena that govern human behavior by closely monitoring and analyzing the mannerisms and actions of diverse individuals in the same environment. The research involves unobtrusively observing individuals of various demographic backgrounds in public spaces, focusing on non-verbal cues and situational contexts. The study seeks to understand how people interact with others, navigate social situations, and respond to external stimuli in real-world settings. Key objectives include identifying similarities and differences in social behaviors, exploring the impact of environmental factors on individual actions, and observing non-verbal communication in social interactions. Additionally, the research investigates the influence of cultural and contextual variables on observed behaviors to provide insights into the complexities of human behavior. The study was conducted in Barcelona, Spain, with 10 cases for observing and interview-short conversations with some random groups. The findings have implications for understanding social dynamics, developing effective communication strategies, and understanding why people behave in specific ways based on our experience and receiving data according to the people and environment information.